A Systematic Review of Race/Ethnicity and Parental Treatment Decision-Making. (October 2018) - Harris, Vandra C.; Links, Anne R.; Walsh, Jonathan; Schoo, Desi P.; Lee, Andrew H.; Tunkel, David E.; Boss, Emily F.
Patient race/ethnicity affects health care utilization, provider trust, and treatment choice. It is uncertain how these influences affect pediatric care. We performed a systematic review (PubMed, Scopus, Web of Science, PsycINFO, Cochrane, and Embase) for articles examining race/ethnicity and parental treatment decision-making, adhering to PRISMA methodology. A total of 9200 studies were identified, and 17 met inclusion criteria. Studies focused on treatment decisions concerning end-of-life care, human papillomavirus vaccination, urological surgery, medication regimens, and dental care. Findings were not uniform between studies; however, pooled results showed (1) racial/ethnic minorities tended to prefer more aggressive end-of-life care; (2) familial tradition of neonatal circumcision influenced the decision to circumcise; and (3) non-Hispanic Whites were less likely to pursue human papillomavirus vaccination but more likely to complete the vaccine series if initiated. The paucity of studies precluded overarching findings regarding the influence of race/ethnicity on parental treatment decisions. Further investigation may improve family-centered communication, parent engagement, and shared decision-making.